The Breast Tumor Microenvironment: Could Silicone Breast Implant Elicit Breast Carcinoma? - Fleury E; Nimir C; D'Alessandro GS (Breast Cancer: Targets and Therapy, 2021)
Eduardo Fleury,1 Cristiane Nimir,2 Gabriel Salum D’Alessandro3 1Service of Radiology, IBCC – Instituto Brasileiro de Controle do Câncer, São Paulo, SP, Brazil; 2Service of Pathology, FEMME – Laboratório da Mulher, São Paulo, SP, Brazil; 3Service of Plastic Surgery, IBCC – Instituto Brasileiro de Controle do Câncer, São Paulo, SP, BrazilCorrespondence: Eduardo FleuryService of Radiology, IBCC – Instituto Brasileiro de Controle do Câncer, Rua Maestro Chiaffarelli, 409, São Paulo, SP ZIP 01432-030, BrazilEmail edufleury@hotmail.comAbstract: Complications related to breast implants have received much attention recently. Breast implant-associated anaplastic large cell lymphoma, silicone-induced granuloma of breast implant capsule, and breast implant illness are the main complications reported in the medical literature. However, the literature contains limited evidence regarding the possibility of silicone implants eliciting breast carcinoma. In this manuscript, we propose a theory in which the immune response to silicone breast implant gel bleeding acts as a triggering point for tumor oncogenesis in breast tissue. This hypothesis is derived from our findings of a case of invasive and undifferentiated medullary carcinoma in a patient with a silicone breast implant. The following concepts have been used to support this theory: 1) silicone bleeding from intact breast implants; 2) metaplasia: an adaptation to injury and precursor to dysplasia and cancer; 3) T-cell dysfunction in cancer immunity; 4) inhibitory cells in the tumor microenvironment (TME); 5) morphogenesis and bauplan; and 6) concepts underlying medullary carcinoma. We propose that the inflammatory process in response to silicone particles in the pericapsular glandular tissue favors the development of cellular mutations in specialized epithelial cells. This reverse morphogenesis could have resulted in breast carcinoma of the medullary type in the present case.Keywords: breast implant-associated anaplastic large cell lymphoma, BIA-ALCL, breast implant illness, BII, silicone granuloma, breast cancer, breast implant